(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
The rapid development of multiple technology has greatly affected the products and architectural details becoming they do not belong to a particular identity, and was influenced by western forms, and the products expressed their compositions and details about the individual’s influence on contemporary architectural movements and the absence of their relationship with the identity of the individual and society, Thus it negatively affects the identity of local architecture, the problem of research was the existence of a knowledge gap about the impact of contemporary technology in the generation of architectural styles, but the objective of the research is to study the impact of contemporary technology on the generation architectural details represented by architectural styles, research assumes new styles derived from local architectural styles with a local identity can be generated that reflect the values of society and are influenced by technological development .The practical study included the analysis of Western architecture and Arab and local architectural products based on the concept of technological evolution and the generation of architectural styles by studying the architectural details represented by the elevations of buildings. The research has found will be used architectural styles read from local architecture in architectural productions influenced by technological development, and it is possible to depended on the vocabulary of generation to produce architectural styles that are keeping with technological development and linked to the identity of contemporary local architecture.